Recruitment and retention of allied health professionals in the disability sector in rural and remote New South Wales, Australia. Issue 1 (2nd January 2014) - Lincoln, Michelle; Gallego, Gisselle; Dew, Angela; Bulkeley, Kim; Veitch, Craig; Bundy, Anita; Brentnall, Jennie; Chedid, Rebecca Jean; Griffiths, Scott
Abstract: Background  People with disability living in rural areas are vulnerable to the loss of access to allied health services due to a critical shortage of allied health professionals (AHPs). This study aimed to investigate recruitment and retention issues of importance to AHPs providing services to people with disability in rural New South Wales, Australia. Method  Focus groups and semistructured interviews were conducted with 97 purposively sampled service providers in the disability sector. Interviews and focus groups were digitally recorded and transcribed. A modified grounded theory approach using thematic analysis and constant comparison was used to analyse the data. Results  Three major themes relating to recruitment and retention were identified: (a) flexible recruitment, (b) retention strategies that work, and (c) challenges to retention. Conclusions  AHPs in the disability sector identified some of the same issues influencing recruitment and retention as AHPs in the health, education, and private sectors. Several unique issues were also identified that will assist policymakers to improve recruitment and retention of AHPs employed in the disability sector in rural areas.